Involvement of oxidative stress and calcium signaling in airborne particulate matter - induced damages in human pulmonary artery endothelial cells. (December 2017) - Deweirdt, J.; Quignard, J.F.; Crobeddu, B.; Baeza-Squiban, A.; Sciare, J.; Courtois, A.; Lacomme, S.; Gontier, E.; Muller, B.; Savineau, J.P.; Marthan, R.; Guibert, C.; et al.
Abstract: Recent studies have revealed that particulate matter (PM) exert deleterious effects on vascular function. Pulmonary artery endothelial cells (HPAEC), which are involved in the vasomotricity regulation, can be a direct target of inhaled particles. Modifications in calcium homeostasis and oxidative stress are critical events involved in the physiopathology of vascular diseases. The objectives of this study were to assess the effects of PM2.5 on oxidative stress and calcium signaling in HPAEC. Different endpoints were studied, (i) intrinsic and intracellular production of reactive oxygen species (ROS) by the H2 DCF-DA probe, (ii) intrinsic, intracellular and mitochondrial production of superoxide anion (O2 − ) by electronic paramagnetic resonance spectroscopy and MitoSOX probe, (iii) reactive nitrosative species (RNS) production by Griess reaction, and (vi) calcium signaling by the Fluo-4 probe. In acellular conditions, PM2.5 leads to an intrinsic free radical production (ROS, O2 − ) and a 4 h-exposure to PM2.5 (5–15 μg/cm 2 ), induced, in HPAEC, an increase of RNS, of global ROS and of cytoplasmic and mitochondrial O2 − levels. The basal intracellular calcium ion level [Ca 2 + ]i was also increased after 4 h-exposure to PM2.5 and a pre-treatment with superoxide dismutase and catalase significantly reduced this response. This study provides evidence that the alteration of intracellular calcium homeostasis induced by PM2.5 is closely correlated to an increase of oxidative stress. Highlights: PM2.5 increased both reactive oxidative and nitrosative species (ROS/RNS) in HPAEC. PM2.5 impaired calcium signaling and nitric oxide (NO) bioavailability in HPAEC. PM2.5 -induced alteration of intracellular calcium homeostasis was correlated to ROS. PM2.5 exposure may be a risk factor for exacerbation of preexistent vascular disease.